The Term Structure of Bond Liquidity - Gehde-Trapp, Monika; Schuster, Philipp; Uhrig-Homburg, Marliese (Journal of Financial and Quantitative Analysis, 2018)
We analyze the impact of market frictions on the trading volume and liquidity premia of finite-maturity assets when investors differ in their trading needs. Our equilibrium model generates a clientele effect (frequently trading investors hold only short-term assets) and predicts i) a hump-shaped relation between trading volume and maturity, ii) lower trading volumes of older compared with younger assets, iii) an increasing liquidity term structure from ask prices, iv) a decreasing or U-shaped liquidity term structure from bid prices, and v) spillovers of liquidity from short-term to long-term maturities. Empirical tests for U.S. corporate bonds support our theoretical predictions.